Implementasi Teknologi Pembayaran Nontunai (TERANO) Dalam Pembayaran Pajak Bumi Dan Bangunan Di Desa Monggolito (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2025)
Introduction/Main Objectives: implementation of non-cash payment technology (TERANO) in paying land and building taxes in Monggolito Village, using George C. Edward III's policy implementation theory. Background Problems: The background of the study is based on obstacles to the implementation of the TERANO systern such as low digital literacy, public stigma, and limited facilities and infrastructure.  Novelty: The novelty of this research lies in the implementation of the TERANO system at the village level using George C. Edward III's policy implementation theory, which includes indicators of communication, resources, disposition, and bureaucratic structure. Research Methods: This research uses a qualitative method with a case study approach. Data collection techniques are carried out through interviews, observations, and documentation involving 7 informants as sources. Data analysis techniques utilise the stages of data reduction, data presentation, and drawing conclusions. Finding/Results: The results of the study show that the implementation of the TERANO system has not been optimal. The four indicators in Edward III's theory of communication, resources, disposition, and bureaucratic structure have not been implemented effectively. The communication indicator is limited to socialization and is not evenly distributed The resource aspect, both human resource readiness and facilities and infrastructure, is still not supportive. The implementer's disposition indicator shows a lack of commitment and limited access to technology, and the bureaucracy indicator shows a lack of understanding of the procedures and flow of using TERANO. Conclusion: The implementation of TERANO cashless payment technology in Property and Land Tax using Edward III's theory is not yet running optimally in Monggolito Village due to constraints in communication, resources, disposition, and bureaucracy.
Keywords: TERANO; Pajak Bumi dan Bangunan; Implementasi